Adolescent Psychological Assistance Treatment Strategy Integrating Home-School Coordination and Network Information - Yaling Li (Occupational Therapy International)
With the continuous satisfaction of material life, teenagers’ physical health has been generally improved, and all aspects of competition have posed a challenge to teenagers’ mental health. Therefore, both at the family level and at the school level, teenagers’ mental health education has been paid more and more attention. The school cooperative education model came into being, which has had an important impact on the mental health education of teenagers. Family education is the first level of education for teenagers. Parents’ role model, family education concept, and education model all play a key role in the development of children’s mental health. Based on this, this paper will focus on optimizing the home-school cooperation strategy, further clarify the main responsibilities of the school, teachers, and parents in the home-school cooperation education in the strategy, establish and improve the home-school cooperation mechanism based on this, and focus on the cultivation of parents’ mental health education and teachers’ mental health guidance professional skills in this process. Based on the current situation of network home-school mental health coordination and mental health education, this study takes teenagers as the research object, aiming at the common psychological problems in learning, social adaptation, and interpersonal communication, and tries to study the problems of promoting teenagers’ mental health from the perspective of integrity and development. The developed home-school collaboration method is to verify that the network home-school collaboration method is more effective than the traditional home-school collaboration method in promoting the mental health development of primary school students, so as to provide a reference for the theory and practice of home-school collaboration under the network environment to carry out mental health education. According to the corresponding network information intelligent algorithm, this paper constantly adjusts the coordination strategy between family and school and guides teenagers to internalize the corresponding excellent behaviour into their own habits. In the experimental part, the psychological assistance treatment scheme proposed in this paper is verified and analysed. The experimental results show that the psychological assistance treatment program for adolescents proposed in this paper has obvious effects. School education has a special mental health counseling center and special psychological teachers, which can carry out mental health education more scientifically. The unity and cooperation between family education and school education can combine the educational power of parents and schools to fully develop the mental health of teenagers.